Pengembangan Alat Bantu Latihan Shooting Three Point “Portable Knee Touch” Dalam Permainan Bola Basket - Muh Isna Nurdin Wibisana; Difa Arya Saputra; Bertika Kusuma Prastiwi (Jurnal Sport Science, 2023)
Three point shoot is a three point shot technique. These shots are usually only taken outside the line which is worth three points. At the time of initial observation, the position of the student's knees were too forward which made the body movements when shooting unbalanced and the movements were ineffective so that the ball did not reach the hoop and go in. This is what often happens, a cause of errors that are often not seen by coaches who are too focused on hand movements. therefore the researcher wants to develop a tool for three point shooting practice. The purpose of this research is to develop a shooting practice tool (three point shoot) which is used to help practice shooting techniques in basketball practice. This type of research was conducted using the "Research and Development" approach. In Research and Development research it is used to produce a three-point shooting tool called the portable knee touch. The sample in this study were extracurricular participants at SMP Negeri 1 Kedungwuni 30. The instrument was in the form of questions given to respondents to fill out a questionnaire containing respondents' opinions about the portable knee touch tool to help practice three point shooting. The instrument is made with 4 answer choices consisting of point 4 which means very good, point 3 means good, point 2 means less, point 1 means very less. The results of the data obtained from research by material experts amounted to 83.33% and media experts by 80%. Large-Scale Trials, with the results of large-scale respondents of 87.36% can be categorized as appropriate for use as a three-point shooting training aid in basketball games